Management Information Systems Requirements and Their Role in Achieving Strategic Excellence: An Analytical Study of the Opinions of a Sample of Managers in Private Sector Banks in Erbil - احمد اسماعيل جبرائيل; صابر عبدالله سامي; كمال نوري عبدالرزاق (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
General framework: The general framework represents the study problem, which was identified by raising several questions about the nature of the relationship, the impact, and the variance between the independent variable the requirements of management information systems, and the dependent variable strategic excellence. All hypotheses were subjected to multiple tests, and the study used a questionnaire as a tool to obtain data. Objective: The current study aimed to explore the role of the requirements of management information systems in achieving strategic excellence; the dimensions of the requirements of management information systems, were the availability of physical requirements, software requirements, human requirements, organizational requirements and databases. While the dimensions of strategic excellence were general strategy, superiority of human resources, superiority of leadership, superiority of culture, superiority of services Study methodology: The study followed the descriptive analytical approach, as the main and sub-variables were described, as well as analyzing the relationships and influence between the variables. The study used descriptive statistics and some other statistical measures to measure the variables. The study tested its hypotheses on the managers of private banks in the city of Erbil, which numbered (152) managers, representing the study sample in (44) banks representing the study community, these hypotheses were tested by applying statistical methods using the computer program and symbolized by (SPSS V.22). Main Results: The study reached several conclusions represented in the realization of most of the hypotheses to varying degrees, the existence of a positive and important relationship between management information systems and strategic superiority at the macro and micro levels, and the surveyed banks benefiting from the requirements of management information systems in achieving their strategic superiority and providing them with a greater opportunity to create an added value in providing its services and use of information technology to beat competitors and focus on market segmentation. Main Recommendations: The researcher recommended the surveyed banks to pay attention and focus on the requirements of management information systems and strategic excellence in their work. The study also provided some suggestions for future studies.